New dynamics of the conflict between two sides in schools - Ortega Gil, Pablo (Avances en Supervisión Educativa, 2016)
This paper contains my own thoughts concerning what I have called new dynamics of the conflict between two sides in Schools. It begins by presenting the contrast between traditional conflicts, where both sides believed their argument was a private affair, and these new dynamics where one or both sides of the conflict tend to make it public and work to win support for their cause. The furious confrontation some people seek and the waves of indignation they set off bring to mind the frequent social media shitstorms we hear about. As a consequence, as the conflict festers, the inspector of education receives countless visits, phone calls and protest letters, an uproar designed to influence her decision. Next, some real cases are discussed, although no information is given of the people taking parts in the events to safeguard identities. Finally, I propose a checklist that involves a sequence of steps designed to protect the inspector from pressure and help her deal more efficiently with problems of this nature.